2016
DOI: 10.21037/qims.2016.07.01
|View full text |Cite
|
Sign up to set email alerts
|

Can MRI accurately detect pilon articular malreduction? A quantitative comparison between CT and 3T MRI bone models

Abstract: Background: Pilon fracture reduction is a challenging surgery. Radiographs are commonly used to assess the quality of reduction, but are limited in revealing the remaining bone incongruities. The study aimed to develop a method in quantifying articular malreductions using 3D computed tomography (CT) and magnetic resonance imaging (MRI) models.Methods: CT and MRI data were acquired using three pairs of human cadaveric ankle specimens.Common tibial pilon fractures were simulated by performing osteotomies to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…This merging, either by SVD or ICP registration procedures, is still considered as the gold standard to obtain reconstructions of complete anatomical models of the diarthrodial joints, which can include the bones and the cartilage in between. The alternative would be defining these bones plus cartilage models from MRI scans only, but our present results show that the accuracy of the MRI-based bone models is higher than that of the gold STCT-based models, though a number of studies have claimed comparable results (20,(35)(36)(37)(38)(39)(40). MRI-based 3D models of the bone have shown comparable accuracy with respect to CT-based models (35)(36)(37)40,41), even in presence of normal and dysplastic anatomical structures (37).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This merging, either by SVD or ICP registration procedures, is still considered as the gold standard to obtain reconstructions of complete anatomical models of the diarthrodial joints, which can include the bones and the cartilage in between. The alternative would be defining these bones plus cartilage models from MRI scans only, but our present results show that the accuracy of the MRI-based bone models is higher than that of the gold STCT-based models, though a number of studies have claimed comparable results (20,(35)(36)(37)(38)(39)(40). MRI-based 3D models of the bone have shown comparable accuracy with respect to CT-based models (35)(36)(37)40,41), even in presence of normal and dysplastic anatomical structures (37).…”
Section: Discussionmentioning
confidence: 53%
“…This is expected to lead to a better accuracy in 3D bone modelling and therefore prosthesis design, because of a thorough representation of the patient-specific bone and joint morphology. Particularly, within high-resolution medical imaging technologies, such as computed tomography (CT) and magnetic resonance imaging (MRI), identification of anatomical structures are achieved (13,(18)(19)(20)(21), traditionally for bone segments and soft tissues including the cartilage, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of measuring Noise before and after the distribution of ® . The reason why there was a difference in Noise before and after the distribution of 99m Tc was because of attenuation phenomena of X-ray due to dense substances such as tooth and metal, which occurs artifact [15], and the more attenuation occurs, the more noise will be created. Besides, there is a study that demonstrated that there is an artifact in metal substance used for filling of teeth such as metal, gold, and titanium [16] and it is considered to have a difference in Noise due to 99m Tc metal ion, which is a minute amount of VIIB radioactive metal substance melted in Normal Saline.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the size of artefact produced in Magnetic Resonance imaging is significantly small. 31 Hence, use of titanium screw is recommended as it promotes fracture healing and improves quality of post-operative assessment and detection of avascular necrosis of femoral head.…”
Section: Choice Of Implantmentioning
confidence: 99%